More partnership agreements - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
With three new agreements signed in Southern Africa and the Caribbean, CTA s programme of pilot projects in partnership building with independent sector organisations continues to grow. In South Africa, the Land Development Unit at the University...